METASTATIC POORLY DIFFERENTIATED THYROID CANCER: A CASE REPORT - Leong , Beatrice Jia Yen; Lee, Xe Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Poorly differentiated thyroid carcinoma (PDTC) is an aggressive subtype of thyroid cancer, representing 0.23%– 2.6% of cases.¹ Due to its rarity, the role of thyroglobulin (Tg) monitoring and the effectiveness of radioactive iodine (RAI) ablation have not been clearly defined. Elevated Tg levels in PDTC are associated with higher recurrence suggesting prognostic significance. While RAI avidity is variable, 25% of PDTC cases maintain the ability to uptake iodine. In such cases, RAI ablation significantly improves survival after thyroidectomy. CASE A 51-year-old female presented to a private hospital with a one-year history of neck swelling in April 2023. Initial blood investigations, including thyroid function tests were normal and she was advised that no surgical intervention was necessary. There was progressive enlargement of the neck, and by January 2024, she developed airway compression. CT scan showed a large multinodular goiter, an ill-defined hypodense mass in the left thyroid lobe and pulmonary nodules measuring 0.5–2 cm suggesting metastases. She underwent total thyroidectomy and histopathology confirmed PDTC with lymphovascular spread (pT3aNx, high risk). She was referred to Endocrinology post-thyroidectomy and was started on TSH suppression therapy and given RAI ablation (150 mCi) in April 2024. Baseline stimulated Tg was >500 ng/mL with negative anti-Tg antibodies. CONCLUSION This is the first case of PDTC in our center. A multidisciplinary team was important in management. Our case highlights the prognostic role of Tg, the need for more evidence on the efficacy of each treatment modality and the importance of a standardized treatment algorithms for PDTC.